INDONESIAN HIGH SCHOOL STUDENTS’ ABILITY IN COMPREHENDING NARRATIVE TEXTS - Damayanti, Eka; Supriusman, Supriusman; Azhar, Fadly (International Journal of Educational Best Practices, 2024)
This quantitative descriptive research aimed to find the abilities of the students at one school in Riau Island Province in comprehending narrative texts. The population was 80 students. 28 students were taken as the sample selected by using a purposive sampling technique. The instrument to collect the data was a reading test. The reading test consisted of 5 short narrative texts. Each consists of 8 questions that cover the components of reading such as factual information, main ideas, meaning of certain words, references, and inferences, then the components of narrative texts such as generic structures, language features, and social functions. To analyze the data, the writer calculated the data by using Microsoft Excel 2016. The data analysis showed that the mean score of their ability in comprehending components of reading was 47% while comprehending narrative texts at 53% so their total at 50% and categorized into medium level. The finding of research also showed that the lowest ability for students was in answering questions about finding the meaning of certain words at 43%. It is suggested that students must do more practice in reading, then they should learn more about the eight components of reading comprehension of narrative texts such as factual information, main ideas, vocabulary, references, inferences, generic structure, language features, and social functions. Then learn reading strategy’s such as schema, skimming and scanning.